MENINGKATKAN HASIL BELAJAR GEOGRAFI MENGGUNAKAN BLENDED LEARNING MODEL PEMBELAJARAN FLIPPED CLASROOM PADA PESERTA DIDIK KELAS X MIPA 1 SMAN 3 SIMPANG HILIR - Muh Khamid (Sosial Khatulistiwa: Jurnal Pendidikan IPS, 2022)
The purpose of this study was to determine the activity process of each cycle in improving geography learning outcomes and to determine whether there was an increase in geography learning outcomes for the basics of mapping, remote sensing, and Geographic Information Systems (GIS) using the blended learning model of the flipped classroom learning for first-class students. X MIPA 1 SMAN 3 Simpang Hilir. This research is a classroom action research, each cycle consists of one study schedule (study at home) and three times a study schedule (study at school). Each stage of the cycle consists of planning actions, implementing actions, observing actions, and reflecting on actions. The research data were analyzed descriptively. data collection techniques using observation, post test, reports. In cycle 1 there are 17 students who have completed with a percentage of 60.71% and 11 students have not completed with a percentage of 39.29% with an average learning outcome belonging to the sufficient category, which is based on the class average value of 73.21%, while in the cycle 1 1 there are 25 who have completed with a percentage of 89.29% and 3 have not completed with a percentage of 10.71% with an average learning outcome including the good category, namely based on the class average score of 83.57%. Thus there was an increase in the average learning outcomes from cycle 1 to cycle 2 of 10.36 and the number of students' scores in one class increased by 290. Keywords: improve, learning outcomes, flipped classroom